English Language Teachers' Practices of Differentiated Instruction in Mixed-Ability Classrooms - Bhandari, Bhim Lal; Bhandari, Laxman Prasad; Baguinat, Naomie S. (Journal of Languages and Language Teaching, 2025)
Differentiated instruction is a critical educational strategy for addressing the diverse needs of students in mixed-ability classrooms. However, its consistent application remains a challenge due to teachers' comprehension of differentiated instruction, which led to various challenges in DI-based practice. This paper aims to delve deep into English language teachers' practices of differentiated instruction in mixed-ability classrooms using qualitative research design to reveal instructional approaches and learning enhancements in promoting inclusivity and diversity with emphasis on in-depth interviews in gathering data to document four Nepali teachers’ narratives of their DI practices and the problems they face in implementing it in Rupandehi, Nepal public secondary school classrooms. The study reveals three themes, namely: the promotion of a student-centered approach, personalized learning, and classroom diversity and collaboration. It was found that differentiated instruction enhances students’ classroom engagement and fosters inclusion by promoting personalized instruction, collaboration, and diversity. Constraints in DI practice include large class sizes, and issues of teacher training and support, which suggest that teacher education programmes should highlight differentiated instruction as a key pedagogic component of the curriculum to better equip future teachers with strategies to achieve the needs and interests of students with mixed-abilities.